INDIGENOUS WOMEN IN CUENCA AT THE END OF THE COLONIAL PERIOD: INFORMALITY AS A WAY OF SUBSISTENCE - Sinchi Lojano, Elsa Rosario (2021)
The current work addresses, through the analysis of primary and secondary sources, the diverse dynamics that the indigenous population developed around the urban environment of Cuenca, Ecuador, between the end of the xviii century and the beginning of the XIX century. In this context, the area of participation of indigenous women will be highlighted,who achieved an activism in the economic organization through the elaboration of crafts and the commercialization of products.